Ubicomp4D: Infrastructure and interaction for international development-the case of urban Indian slums - Sambasivan, Nithya; Rangaswamy, Nimmi; Cutrell, Edward; Nardi, Bonnie; Cutrell, Ed (11th International Conference on Ubiquitous Computing, UbiComp 2009, 2009)
This paper attempts to re-imagine ubiquitous computing for populations in low-income and information-challenged environments. We examine information infrastructures in mid-sized urban slums of Mumbai and Bangalore in three ways—1) highlighting technologies supporting social networks, 2) examining underlying notions of trust and privacy in building information networks, and 3) discussing protocols and practices around shared access. We then discuss our thoughts on designing for low-income, low-literacy, and resource-challenged communities, presenting new ways to think about the design of ubiquitous technologies for international development. We argue for collaborative exchange between the established strengths of the Information and Communication Technologies for Development (ICT4D) and Ubicomp communities to generate new ways of shaping technologies towards poverty alleviation in previously neglected socio-economic contexts—Ubicomp4D.